An evaluation of library resources, services and use of Kogi state university, Ayigba, library (2013)
This research evaluated the library resources, service and use of Kogi State University Library. Ayigba. The main objective of the research is to find out the varieties of learning resources available: services rendered: and how effectively they are being utilized by the students and staff The survey research design was adopted with the questionnaire serving as the main instrument for data collection. A total of one hundred and twenty (120) respondents were randomly selected from the students and staff but ninety-five of them responded. Descriptive statistical methods were used in analyzing the data generated. The finding identifies some of the problems of academic libraries to include outdated books, inadequate space, noisy environment, and lack of automation of libraries resources. Also the libraries were not adequately staffed.